Fabricating copper and copper/nickel alloy single crystal bead electrodes with a hydrogen–oxygen torch in ambient air - Weicheng Liao; Xin-yi Lin; Yi-wei Chen; Shuehlin Yau; Jing-Jong Shyue (Electrochemistry Communications, 2019)
The use of copper single-crystal electrodes (CSCEs) has revealed the crucial role of electrode structure in electrocatalysis and corrosion. CSCEs, although commercially available, can be prepared in-house by melting the end of a Cu wire to form a single crystal bead (SCB) in ambient air. Unlike the conventional torch used for making Pt and Au SCBs, the torch used in this study allows the Cu bead to cool down to room temperature in a nitrogen stream. The resulting Cu bead is subsequently fabricated into a CSCE with a desired orientation. Copper’s propensity for oxidation does not pose a problem for our method as long as the H2 and O2 fluxes to the flame are well-controlled. The bulk oxide in the Cu SCB prepared as above is below the detection limit of our X-ray photoelectron spectrometer. The devised method opens up an avenue toward the study of electrochemistry at well-defined Cu and possibly other non-noble transition metal electrodes. Moreover, this method can also be used to make alloyed SCBs, as illustrated by the successful fabrication of a Cu/Ni (98.5/1.5) bead. The resulting Cu(1 1 1) and Cu98.5Ni1.5(1 1 1) electrodes are examined by cyclic voltammetry and in situ scanning tunneling microscopy in 0.1 M sulfuric acid. The trace amount of Ni in the Cu(1 1 1) electrode affects the potential, but not the structure, of specific adsorption of the (bi)sulfate anion. A (√3 × √7)–HSO4− structure and the Cu(1 1 1) lattice are imaged by STM at positive and negative potentials. Keywords: Copper single crystal electrode, Preparation and characterization, Annealing and quenching method